Erectile dysfunction in young patients and elderly patients by sexual encounter profile: A comparative study. (1st March 2022) - Yamagishi, Motoki; Ogushi, Yuta; Niikura, Ayana; Ohta, Tomoka; Ichimura, Yuki; Hashimoto, Yu; Kurokawa, Ippei; Sugishita, Hiroo; Tanifuji, Satoru; Imamura, Yuichiro; Shimoyama, Hideaki; Hayashi, Keiichiro; et al.
Abstract : Objective: Demand for erectile dysfunction treatments has increased not only in elderly patients but also in young patients. Reports indicate that frequent causes of erectile dysfunction in Japan are organic disorders in elderly patients and psychogenetic disorders in young patients. Methods: We defined patients under the age of 40 as young erectile dysfunction patients, and those over 65 as elderly erectile dysfunction patients. We divided these two groups and conducted a retrospective comparative study based on medical questionnaires. We selected 215 cases of patients under the age of 40, and 176 cases of patients over the age of 65, and created a group of young patients and a group of elderly patients. We implemented the erectile hardness score, Sexual Health Inventory for Men, and sexual encounter profile questions 2 and 3 as the patient's daily clinical journal. Results: The median age of young patients was 36 years, and that of elderly patients was 70 years. With respect to Sexual Health Inventory for Men, the average score was a significantly higher score in the young patients (9.26 vs 7.10, P  < 0.001). Concerning erectile hardness score, young patients showed significantly higher scores in erectile hardness score (3.15 vs 2.06, P  < 0.001). In terms of sexual encounter profile question 2, 50.9% of young patients responded "yes, " but 24.3% of elderly patients responded, thus indicating a significantly higher score in young patients. In terms of sexual encounter profile question 3, 6.1% of young patients responded "yes, " and 0.7% of elderly patients responded "yes, " indicating a significantly higher in young patients. Conclusions: The results showed that many young patients with erectile dysfunction were able to perform insertion, but were unable to maintain erection.